Comparative transcriptome and metabolome analysis revealed diversity in the response of resistant and susceptible rose (Rosa hybrida) varieties to Marssonina rosae - Song, Jurong; Chen, Feng; Lv, Bo; Guo, Cong; Yang, Jie; Guo, Jiaqi; Huang, Li; Ning, Guogui; Yang, Yuanyuan; Xiang, Fayun (Frontiers in Plant Science, 2024)
Rose black spot disease caused by Marssonina rosae is among the most destructive diseases that affects the outdoor cultivation and production of roses; however, the molecular mechanisms underlying the defensive response of roses to M. rosae have not been clarified. To investigate the diversity of response to M. rosae in resistant and susceptible rose varieties, we performed transcriptome and metabolome analyses of resistant (KT) and susceptible (FG) rose varieties and identified differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs) in response to M. rosae at different time points. In response to M. rosae, DEGs and DAMs were mainly upregulated compared to the control and transcription factors were concentrated in the WRKY and AP2/ERF families. Gene Ontology analysis showed that the DEGs of FG were mainly enriched in biological processes, such as the abscisic acid-activated signaling pathway, cell wall, and defense response, whereas the DEGs of KT were mainly enriched in Golgi-mediated vesicle transport processes. Kyoto Encyclopedia of Genes and Genomes analysis showed that the DEGs of both varieties were concentrated in plant–pathogen interactions, plant hormone signal transduction, and mitogen-activated protein kinase signaling pathways, with the greatest number of DEGs associated with brassinosteroid (BR) in the plant hormone signal transduction pathway. The reliability of the transcriptome results was verified by qRT-PCR. DAMs of KT were significantly enriched in the butanoate metabolism pathway, whereas DAMs of FG were significantly enriched in BR biosynthesis, glucosinolate biosynthesis, and tryptophan metabolism. Moreover, the DAMs in these pathways were significantly positively correlated with the DEGs. Disease symptoms were aggravated when FG leaves were inoculated with M. rosae after 24-epibrassinolide treatment, indicating that the response of FG to M. rosae involves the BR signaling pathway. Our results provide new insights into the molecular mechanisms underlying rose response to M. rosae and lay a theoretical foundation for formulating rose black spot prevention and control strategies and cultivating resistant varieties.